PENGARUH RISIKO INFLASI, RISIKO SUKU BUNGA, RISIKO VALUTA ASING TERHADAP RETURN SAHAM - Olivia Luthfiah Mufida; Gusganda Suria Manda (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This research was conducted to show the importance of company managers in managing stock returns during inflation, increases in interest rates, and increases in foreign exchange rates. The purpose of this study is to analyze the effect of inflation risk, interest rate risk, and foreign exchange risk on stock returns, 2012-2019 study period. The method in this research is using multiple linear regression analysis. Techniques in conducting this research using quantitative descriptive analysis and obtained 8 companies as research samples. The results of this study indicate that inflation risk has an insignificant effect and the relationship is partially positive influence on stock returns, interest rate risk has no significant effect and partially negative influence on stock returns, foreign exchange risk has a significant effect and the relationship is negative influence significantly partial to stock returns. This research is inseparable from the limitations of the researcher. For investors and potential investors who want to invest, it is better if they pay more attention to the company's financial condition so that investors can find out whether it is feasible or not to invest in the chosen company so that investors do not experience losses.